Guest Edited Collection: Epigenetics within the tumor microenvironment - Aamir Ahmad (Scientific Reports, 2022)
Abstract The tumor microenvironment (TME) comprises of components that exist within the immediate vicinity of tumor cells, including fibroblasts, immune cells, the extracellular matrix, and more. Significant advances have been made in recent years in our understanding of the components of TME and their mutual interactions. Part of the focus of this research has been on epigenetic events, which are increasingly being recognized for their importance in gene regulation and cancer progression. The Collection represents the gradual growth in our understanding of the overall process of how cancer progresses, along with the factors that play a decisive role in this progression. It features studies conducted on models representing many different cancers, and includes mechanistic reports conducted using appropriate in vitro models, studies that analyzed human cancer patients-derived specimens, clinical trials and, additionally, studies involving bioinformatics, metabolomics, chemical libraries screening, next-generation sequencing, and single-cell analysis approaches.